How to kill things with words : Ananias and Sapphira under the Prophetic Speech-Act of Divine Judgment (Acts 4.32-5.11) /: Ananias and Sapphira under the Prophetic Speech-Act of Divine Judgment (Acts 4.32-5.11). (2011) - Unknown
No abstract available